Combination Therapy with Corticosteroids and Mycophenolate Mofetil in the Management of Pemphigus Vulgaris: A Case Report - Ella Finarsih; Kristo Alberto Nababan (GLOBAL HEALTH SCIENCE GROUP, 2026)
Pemphigus vulgaris (PV) is a rare, potentially life-threatening autoimmune blistering disease caused by IgG autoantibodies against desmoglein proteins, leading to acantholysis and intraepidermal blister formation. The incidence of PV ranges from 0.76 new cases per million population per year in Finland to approximately 3.5 new cases per million population per year in other regions. Early diagnosis and appropriate immunosuppressive therapy are crucial to prevent disease progression and complications. This study aims to report the clinical presentation, diagnostic approach, and therapeutic outcome of combination therapy using systemic corticosteroids and mycophenolate mofetil in a patient with pemphigus vulgaris. This is a descriptive case report of a 40-year-old female diagnosed with pemphigus vulgaris. Clinical evaluation, histopathological examination, and therapeutic response were documented and analyzed. A 40-year-old woman who presented with a one-week history of painful, generalized flaccid bullae and erosions involving the face, scalp, trunk, and extremities. Histopathological examination revealed suprabasal intraepidermal blistering with a characteristic row of tombstones appearance, confirming the diagnosis of pemphigus vulgaris.Initial treatment with systemic corticosteroids resulted in partial clinical improvement; however, new lesions continued to develop. The addition of mycophenolate mofetil as a steroid-sparing agent led to significant disease control, with cessation of new blister formation and gradual healing of existing lesions. The patient showed marked clinical improvement with good functional and vital prognosis, although long-term remission remains uncertain. This case highlights a severe and extensive presentation of pemphigus vulgaris and emphasizes the importance of clinicopathological correlation for accurate diagnosis. Early combination therapy with systemic corticosteroids and mycophenolate mofetil may be effective in controlling refractory disease and minimizing corticosteroid-related adverse effects.